An experiment on bribery, tenure duration, and punishment severity in the Indonesian public finance context - Nugroho, Wisnu Setiadi; Winardi, Rijadh Djatu; Wijayanti, Amanda; Permana, Yudhistira Hendra; Sanjaya, Muhammad Ryan (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
Against the backdrop of increasing concern over corruption, this study delves into a laboratory experiment investigating the intricate dynamics of bribery concerning the duration of official tenures and the efficacy of punitive measures. Experimental methods prove pivotal in unraveling the complexities inherent in corrupt behaviors. The study unfolds a compelling pattern, shedding light on the interplay between public officials and civilians, particularly emphasizing the impact of officials' tenure duration on bribery. It brings forth a crucial correlation between familiarity with officials and a heightened likelihood of bribery, with extended tenures amplifying this susceptibility. The concept of "fixed pairing" accentuates the role of prolonged official incumbency in influencing bribery tendencies. Additionally, introducing punitive measures with financial repercussions proves effective in curbing bribery incidents and associated givebacks, particularly when applied to bribe recipients, suggesting heightened stakes public officials face. The study demonstrates the potential of dual treatments involving random pairings and punitive approaches to reduce the magnitude of bribes and givebacks. This study underscores the necessity of curtailing prolonged official tenures to mitigate bribery tendencies, offering insights into enhanced governance and ethical conduct through strategic rotational shifts and robust penalties. These comprehensive findings contribute valuable perspectives to addressing corruption and enhancing ethical standards within public institutions.